PENERAPAN AKUNTANSI PADA USAHA MIKRO KECIL DAN MENENGAH (UMKM) DI KECAMATAN LOWOKWARU KOTA MALANG - Maya Aulia (Jurnal Ilmiah Mahasiswa FEB, 2018)
This aim of this research is to provide an overview about the implementation ofaccounting in Micro, Small, and Medium Enterprises (MSMEs) and to explain thedifficulties encountered in its practice as well as knowledge of owners aboutfinancial accounting standards (SAK EMKM). This research is a qualitativedescriptive research and the data were collected through questionnaires andinterviews. The object of the research is owner of Micro, Small, and MediumEnterprises (MSMEs) located in the Lowokwaru sub-district of thee City ofMalang. Using the purposive sampling method, 41 respondents in total werecollected. The results of the research indicated that most of Micro, Small, andMedium Enterprise (MSME) owners have understood about SAK EMKM. Thenformation in the financial statements is still presented very simply andmanually. The difficulties encountered by owners are the lack of training courseson financial statements and SAK EMKM by practitioners, lack of time, theirprejudice that financial statements are difficult to understand, and the lowawareness to improve financial statements in accordance with SAK EMKM.Keywords: Implementation of Accounting, Micro, Small, and Medium Enterprises(MSMEs), Financial Accounting Standards for Micro, Small, and MediumEnterprises.